New soliton solutions of nonlinear Kudryashov's equation via Improved tan -expansion approach in optical Fiber: DOI: 10.48129/kjs.12441 - Arshed, Saima; Raza, Nauman; Butt, Asma Rashid; Inc, Mustafa (Kuwait Journal of Science, 2022)
In this article, a newly introduced model nonlinear Kudryashov's equation with anti-cubic non-linearity is considered for extraction of soliton solutions. This model is utilized to depict the propagation of modulated envelope signals which disseminate with some group velocity. To find a solution, an appropriate traveling wave hypothesis is used to covert the given model into a nonlinear ordinary differential equation. An analytical technique, the Improved tan-expansion approach has been employed on the governing model to construct many new forms of dark soliton, singular soliton, periodic soliton, dark-singular combo soliton, and rational solution. The constraint conditions for the existence of these solitons have also been provided. The physical significance of the proposed equation has been provided with a graphical representation of the constructed solutions.